Analisis Aktivitas terhadap Penerapan Fasilitas dalam Ruang Aula di EvFiA LAND School - Simatupang, Nadya Ruthmaida; Anshory, Boike Janus (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Effective school hall design is essential to creating a safe and comfortable learning environment. A case study of EvFiA LAND School in Serang, Indonesia, found several spatial elements that needed further development, such as an inadequate hall stage for activities, a risky play area, and a waiting area that was not entirely comfortable for users. Noise was also a problem when the hall was used for multiple activities simultaneously. The redesign focused on security enhancement, comfort, and efficiency to prevent accidents and create an optimal learning environment.